Optimal prestressing of triple-bay prestressed stayed columns. (November 2017) - Yu, Jialiang; Wadee, M. Ahmer
Abstract: A nonlinear finite element model of a triple-bay prestressed stayed column is developed within the commercial package ABAQUS. A linearly obtained 'optimal prestressing force' that maximizes the critical buckling load is investigated since this quantity has been demonstrated in previous work on single-bay prestressed columns to provide a lower bound to the actual maximum load carrying capacity when compared to experimental results and nonlinear modelling. The ratio of the crossarm to the overall column length, the diameter of the cable stays, the relative lengths of the individual crossarms and the ratio of the initial prestressing force to the aforementioned linear optimal prestress are varied. Measures for the relative efficiency of the main column and the stays are defined and the objective of the optimization study is for the efficiency to be maximized. It is found that the true optimal prestress is generally higher than the equivalent, linearly obtained, quantity but by a significantly reduced factor when compared to an equivalent study for single-bay prestressed stayed columns.